The Cost of Contracting Out Solid Waste Collection in the U.S. and the Consequences of Inefficiency - Zimová, Kateřina; Janíčko, Martin, 1983-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
Previous literature on the question of cost savings from privatization of public services leads to rather ambiguous results. This paper offers an estimation and specification of an explanatory model of factors that produce costs in solid waste collection and disposal. The uniqueness of this model lies in its variables, which derived from various studies corresponding with solid waste collection and disposal in the United States. On one hand, the results indicate a reduction of costs due to privatization of solid waste collection. On the other hand, provision of the service by public monopoly represents a significantly more cost effective choice when compared to a private monopoly. The results suggest that the government undergo a thorough examination of market structure before it decides to contract out.
Vedoucí práce: Martin Janíčko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses